Jaringan Nomologis Rasionalitas Epistemik dengan Inteligensi dan Perfeksionisme - Seisar Winengku Handani; Rahmat Hidayat (Faculty of Psychology, Universitas Gadjah Mada, 2018)
Rationality is a human’s ability to think clearly in order to achieve his goals. Rationality has two types, epistemic and instrumental. Epistemic rationality is related judgment and instrumental rationality is related to decision making. This research aimed to validate the nomological network between epistemic rationality, intelligence, and perfectionism. It also aimed to analyze the latent factor of three variables. The subjects of this research were 67 college students from several universities in Yogyakarta. Data collection was held using CBT to measure epistemic rationality and perfectionism while paper and pencil were used to measure intelligence. The result showed that in measurement level, epistemic rationality did not shape the nomological network with intelligence and perfectionism. However, this research found that three variables had two latent factors based on convergence and divergence factor analysis.